Analisis Presepsi dan Dampak Program Indonesia Pintar Terhadap Keberlanjutan Pendidikan Anak: Studi Kasus Pada Keluarga Penerima Di Desa Kedawungwetan - mochamad fadillah; Daryono Daryono; Mochamad Bayu Firmansyah Bayu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the perceptions and impacts of the Indonesia Smart Program (Program Indonesia Pintar/PIP) on the educational continuity of children from beneficiary families at the village level. The research employs a descriptive qualitative method with a mini-research approach. Six participants were purposively selected as active recipients of the PIP in Kedawungwetan Village. The focus of this study lies in the depth of individual experiences rather than the generalization of findings. The theoretical framework includes economic aspects—such as reducing educational costs and increasing human capital investment—and social aspects, including social support, learning motivation, and family educational aspirations. The findings indicate that the PIP plays a significant role in alleviating educational expenses and supporting the continuity of children’s schooling. However, the program’s effectiveness is constrained by several factors, including the relatively small amount of financial aid, delays in fund disbursement, and the lack of social assistance for beneficiaries. These results emphasize that although the PIP has made a positive contribution to improving educational access for underprivileged families, further policy improvements are needed—particularly in increasing the amount of aid and strengthening social support—to achieve equitable education outcomes more effectively.